2003
DOI: 10.1097/01.asn.0000057854.32413.81
|View full text |Cite
|
Sign up to set email alerts
|

Atubular Glomeruli and Glomerulotubular Junction Abnormalities in Diabetic Nephropathy

Abstract: Abstract. Atubular glomeruli (AG) have been described in several renal disorders. However, little attention has been paid to AG in diabetic nephropathy (DN). Preliminary studies suggested that tip lesions were frequently present in type 1 diabetic (D) patients with proteinuria. The aim of this study was to determine the frequency of AG and their possible relationship with tip lesions in DN. Renal biopsies from eight proteinuric type 1 D patients with normal to moderately reduced GFR (76 Ϯ 26 ml/min per 1.73 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 38 publications
5
77
1
Order By: Relevance
“…These abnormalities were closely associated with tip lesions (glomerular tuft to Bowman's capsule adhesions [TBCA] at GTJ area), a finding reported in a variety of renal diseases with clinical proteinuria (5)(6)(7). This study also found that, along with the classical diabetic glomerulopathy lesions, these GTJA, together with tubulointerstitial parameters, predicted most of the variability in GFR among these proteinuric patients (4). However, because NA and MA patients were not included, the relationship of GTJA and AG to AER could not be assessed in this study.…”
Section: Iabetic Nephropathy (Dn) Remains the Leading Cause Of Esrdsupporting
confidence: 69%
See 3 more Smart Citations
“…These abnormalities were closely associated with tip lesions (glomerular tuft to Bowman's capsule adhesions [TBCA] at GTJ area), a finding reported in a variety of renal diseases with clinical proteinuria (5)(6)(7). This study also found that, along with the classical diabetic glomerulopathy lesions, these GTJA, together with tubulointerstitial parameters, predicted most of the variability in GFR among these proteinuric patients (4). However, because NA and MA patients were not included, the relationship of GTJA and AG to AER could not be assessed in this study.…”
Section: Iabetic Nephropathy (Dn) Remains the Leading Cause Of Esrdsupporting
confidence: 69%
“…Glomeruli that are attached to normal tubules in proteinuric patients are larger than those that are attached to normal tubules of patients in the other type 1 diabetes groups, perhaps representing compensatory hypertrophy. However, as described elsewhere, AG in proteinuric patients are reduced in volume, whereas glomeruli with ATNO are of intermediate size (4).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…While the glomerulus is widely recognized as the primary site of injury in DN, tubular injury is also prominent. Tubular hypertrophy and interstitial inflammation are seen early in the course of DN [46] and with disease progression tubular atrophy and interstitial fibrosis develop in concert with declining renal function [5,7]. Cross-talk between podocytes and the tubular epithelium is believed to play an important role in the development of tubulointerstitial fibrosis and renal functional decline; however, the mechanisms by which this occurs are not fully understood [810].…”
Section: Introductionmentioning
confidence: 99%